Components of integrated thinking: Evidence from South African listed companies - Dusan Ecim (South African Journal of Business Management, 2024)
Purpose: This article explores three components that need to be addressed as part of an integrated thinking strategy and provides evidence on the state of integrated thinking application in a developing economy.